Anchoring Al- and/or Mg-oxides to magnetic biochars for Co-uptake of arsenate and fluoride from water. (1st September 2021) - Shen, Ziyi; Jin, Jie; Fu, Jingjing; Yang, Meng; Li, Feihu
Abstract: The co-occurrence of arsenic and fluoride in the water environment has led to many health concerns for living beings. Simultaneous removal of such ions is crucial to the safety of water resources, and biochar has been extensively engaged to address this issue. Here four magnetic biochars (mBCs) including pristine magnetic biochar and three aluminum (Al) and/or magnesium (Mg) oxides-anchored magnetic biochar (i.e., Al-mBC, Mg-mBC, and MgAl-mBC) were prepared via a facile pyrolysis method and then comprehensively evaluated as adsorbents for enhanced co-uptake of arsenate (As V ) and fluoride (F − ) from synthetic water. The mBC shows a high specific surface area of 205 m 2  g −1, which dropped to 116, 80, and 114 m 2  g −1 upon the anchoring of Al, Mg, and Mg + Al, respectively. Our results suggest that the adsorption of either As V or F − is highly pH-dependent, and pH 4–6 is the optimal range for maximum adsorption. The adsorption isotherm data indicate that the MgAl-mBC adsorbent outranks all other mBCs for co-uptake of both As V and F − . The adsorption capacity maxima of MgAl-mBC are 34.45, and 21.59 mg g −1 for As V and F −, respectively (pH = 5, T  = 10 °C), also highly outstripping other biochars reported in the literature. The magnetic feature of these mBCs enables us to fast reclaim and regenerate the exhausted adsorbents by an external magnet and dilute NaOH. The Al- and Mg-anchored mBCs are expected to be used as highly efficient adsorbents for environmental remediation of waters contaminated by both As V and F − . Graphical abstract: Image 1 Highlights: Metal-anchored magnetic biochars are prepared via a facile pyrolysis method. Magnetic biochars exhibit a high adsorption capacity for both As V and F − . The spent magnetic biochars can be magnetically recycled and fast regenerated. MgAl-mBC adsorbent outranks other biochars for simultaneous removal of both As V and F − .